Eventhub: A Web-Based Intelligent Event Management Platform to Accelerate the Digital Transformation of Event Ecosystems - Ruqayah; Wifda Muna Fatihia (Journal of Applied Informatics Research, 2025)
Digital technologies are rapidly expanding. This shift is transforming event management from a manual and fragmented practice into a systematically engineered process supported by information systems. However, organizers and vendors continue to face inefficiencies due to disjointed workflows, duplicated efforts, and limited transparency among stakeholders. To address these challenges, this study presents EventHub, a conceptual web-based event vendor management platform, with an emphasis on system design and formal modeling rather than full-scale implementation. Utilizing a user-oriented development approach, the research identifies and analyzes both functional and non-functional requirements, which are then modeled using a suite of Unified Modeling Language (UML) diagrams, including use case, activity, sequence, and class diagrams. These models define user roles, interaction scenarios, process flows, and underlying data structures in a coherent and traceable manner, resulting in a comprehensive design blueprint for EventHub. This blueprint is intended to guide future implementation and serve as a reusable reference for similar event management solutions, thereby providing a structured foundation for ongoing digital transformation initiatives within the event management ecosystem.